Sudangrass, sorghum-sudan, forage sorghum, and corn silages and three protein levels for growing yearling steers - Thompson, W.; Oltjen, J.; Bolsen, K.; Ilg, H.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Sudangrass, sorghum-sudan, forage sorghum, and corn silages were full-fed to yearling steers for 70-or 91-day growing periods. For both periods, steers fed corn silage outperformed steers fed any other silage. In the 70-day period silages from both sudangrass and sorghum-sudan cut at 45- and 60-inch plant heights, respectively, supported performance similar to forage sorghum silage. For both periods steers fed sorghum-sudan (dough) silage gained slowest and least efficiently. For the 91-day period, rations containing 12.0% crude protein supported better performance than rations containing 10.5 or 9% protein and 10.5% protein rations supported better performance than 9% protein rations.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Sudangrass; Sorghum-sudangrass; Forage sorghum; Corn silage; Protein; Steers